Developed convolutional encoder and viterbi decoder using C++ - Chin Toong Hing (2023)
A Convolutional encoder (CE) and Viterbi algorithm (VA) is developed using c++ program to demonstrate the encoding and encoding for a 1/2 rate Convolutional encoder. The Convolutional encoder display the ASCH code for any character from keyboard.